Analysis Of 3D Cadastre Situation In Nepal - Paudyal, Dev Raj; Sharma, Rabin Kaji (Journal on Geoinformatics, Nepal, 2006)
The history of cadastre prevails that the records of land are kept in a text form as a basis to collect revenue and could be refer to one dimension cadastre. His Majesty's Government (HMG) of Nepal declared to launch Land Reform Program on 1964 AD. The main purpose of the program was to impose ceiling on land holding. For this purpose, it was necessary to determine the area of land hold by a land owner. In this way, the concept of two dimension cadastre was realized and the land registration was started with the help two dimension cadastral maps. As the population in urban area is ever growing and the land is fixed, the use of space under and above the surface seems to be one of the solutions to address the issue. So, there is a need of registration of vertical dimension of the legal status of real estate objects. The 3D information is becoming essential for land administration in Nepal. HMG of Nepal has adopted a policy to build apartments and joint residential building in urban area for optimal use of available space. Although, some juridical measures exist to address registration of vertical dimension of legal status of real estate objects in the available act, a lot of institutional and technical problems are facing for registration of apartment and room in a multi storey building in Nepal. Therefore, it is necessary to make a good institutional arrangement and develop a system to visualize 3D cadastre to link with cadastral maps and related land records. This paper first investigates the 3D cases practices in Nepal. There are more than eight such issues to be considered for the implementation of 3D cadastre. It then further elaborates about the three aspects; institutional, technical and legal to be considered for the 3D cadastre in Nepal. A low cost solution for the 3D mapping of the apartment or multistory building has investigated. The findings of this research will help the policy makers for the effective implementation of 3D cadastre in Nepal.